P223 THYROTOXIC DILATED CARDIOMYOPATHY. (18th May 2022) - Follesa, F; Cherubini, S; Castelli, F; De Luca, L; Gioffrè, L; Ciolli, A
Abstract: Hyperthyroidism can strongly impact cardiac function. Thyrotoxicosis enhances myocardiocytes metabolism and it can be responsible for hyperdynamic circulation state leading to heart failure with preserved ejection fraction, but also left ventricle dilatation and severe contractile function impairment. It can furthermore provoke arrhythmias, mostly atrial fibrillation, but, as we are going to discuss in this case, even ventricular arrhythmias. A 40–year–old woman came to our emergency department for chest pain. ECG showed reduced R waves voltage in precordial leads and troponin I values were normal. The echocardiogram showed severe left ventricle disfunction with global hypokinesia (EF 35%) and enlarged left ventricle (LVEDD 65 mm). Blood tests revealed severe hyperthyroidism with extremely low level of TSH, FT3 13, 45 pg/ml, FT4 3, 4 ng/ml and thyroid echography documented multiple solid nodular formations with hypo–isoechogenic signal. She underwent a coronary angiography that showed patent coronary arteries, and a cardiac magnetic resonance confirming severe contractile impairment and hypertrabeculation of the apex and lateral wall. On the assumption of a dilated cardiomyopathy secondary to hyperthyroidism, we started treatment with methimazole, ACE inhibitors and propranolol. During hospitalization, continuous ECG monitoring recorded several episodes of non–sustained ventricular tachycardia, the longest lasting 22 seconds, so the patient was discharged with a wearable cardioverter–defibrillator. It did not record any arrhythmias and it was dismissed a month later. After almost two months of therapy, the echocardiogram showed mild left ventricular contractility improvement (EF 45%), and blood tests documented partial reduction of hyperthyroidism. A 24–hour ECG Holter did not record any arrhythmias and the patient remained asymptomatic during all the period after discharge. Even if rare, scientific literature confirms that dilated cardiomyopathy with reduced ejection fraction can occur as a complication of hyperthyroidism. After the exclusion of an ischemic cause, we underline the need for adequate initiation of treatments for thyrotoxicosis and heart failure, in order to improve chance of left ventricular function recovery. In the case discussed, after two months of therapy, EF was still not completely restored but improved from 35% to 45%, and concurrently arrhythmic risk did clearly decrease.